Electro-elastic stress analysis on piezoelectric inhomogeneity-crack interaction - Bai, Jing (2008)
This project investigates the interaction problem of a fiber-shaped piezoelectric inhomogeneity embedded in a non-piezoelectric elastic matrix which contains a crack. The matrix is assumed to be infinite in all directions and the crack is near the piezoelectric fiber. The body is subjected to a far-field in-plane tension and a far-field anti-plane electric field.